2018
DOI: 10.1038/s41467-018-03613-1
|View full text |Cite
|
Sign up to set email alerts
|

The oldest magnetic record in our solar system identified using nanometric imaging and numerical modeling

Abstract: Recordings of magnetic fields, thought to be crucial to our solar system’s rapid accretion, are potentially retained in unaltered nanometric low-Ni kamacite (~ metallic Fe) grains encased within dusty olivine crystals, found in the chondrules of unequilibrated chondrites. However, most of these kamacite grains are magnetically non-uniform, so their ability to retain four-billion-year-old magnetic recordings cannot be estimated by previous theories, which assume only uniform magnetization. Here, we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 27 publications
2
44
0
2
Order By: Relevance
“…MV states have been previously documented through imaging and modeling, especially in the field of materials science (e.g., Donnelly et al., ; Elmurodov et al., ; Gan et al., ; Ivanov et al., ; Kanda et al., ; Xu et al., ) but also in the earth and planetary sciences (Einsle et al, ; Roberts et al, ; Shah et al, ). The key findings of these studies are that MV states are stable in natural and synthetic materials and that their remanent magnetizations are higher than for SV states.…”
Section: Discussion: the Vortex State In Geologic Materialsmentioning
confidence: 99%
“…MV states have been previously documented through imaging and modeling, especially in the field of materials science (e.g., Donnelly et al., ; Elmurodov et al., ; Gan et al., ; Ivanov et al., ; Kanda et al., ; Xu et al., ) but also in the earth and planetary sciences (Einsle et al, ; Roberts et al, ; Shah et al, ). The key findings of these studies are that MV states are stable in natural and synthetic materials and that their remanent magnetizations are higher than for SV states.…”
Section: Discussion: the Vortex State In Geologic Materialsmentioning
confidence: 99%
“…With the exception of Winklhofer et al (12) and Fabian et al (13), all previously published Pullaiah curves found in the literature, e.g., Pullaiah et al (9) and Garrick-Bethell and Weiss (14), are based entirely on SD theory, which does not take into account more complex magnetic domain structures such as the flower and single-vortex (SV) states (15). We know such nonuniform structures are ubiquitous in the vast majority of iron particles found in planetary materials (16)(17)(18). In fact, near-equant iron SD particles are theoretically thermally unstable at room temperature; i.e., they are superparamagnetic (19)(20)(21) with relaxation times of seconds, not billions of years.…”
Section: Paleomagnetic Observations Provide Valuable Evidence Of the mentioning
confidence: 99%
“…Once these energy barriers are found, they can be used to obtain relaxation times from the Arrhenius equation also used in Néel's SD and MD theories. This process has to be repeated for all temperatures in question and all grain sizes, geometries, and minerals of interest and has been done for magnetite cubes (Muxworthy et al, 2003) and more recently using the general micromagnetic model MERRILL (Conbhuí et al, 2018) for equidimensional magnetite cuboctahedra (Nagy et al, 2017), for greigite octahedra (Valdez-Grijalva et al, 2018), and for iron cubes (Shah et al, 2018). While such micromagnetic models are on the rise and are undoubtedly physically most accurate, they have a number of shortcomings: (1) the great computing power necessary to calculate large particles limits them mostly to the PSD range, that is, vortex states rather than true MD states that contain DWs;…”
Section: Numerical Models Of MD Thermoremanencementioning
confidence: 99%
“…Once these energy barriers are found, they can be used to obtain relaxation times from the Arrhenius equation also used in Néel's SD and MD theories. This process has to be repeated for all temperatures in question and all grain sizes, geometries, and minerals of interest and has been done for magnetite cubes (Muxworthy et al, ) and more recently using the general micromagnetic model MERRILL (Conbhuí et al, ) for equidimensional magnetite cuboctahedra (Nagy et al, ), for greigite octahedra (Valdez‐Grijalva et al, ), and for iron cubes (Shah et al, ). While such micromagnetic models are on the rise and are undoubtedly physically most accurate, they have a number of shortcomings: (1) the great computing power necessary to calculate large particles limits them mostly to the PSD range, that is, vortex states rather than true MD states that contain DWs; (2) as the model has to be run for a particular grain geometry, a nearly infinite number of calculations would have to be done to cover all naturally occurring grain sizes and shapes; (3) unlike simple models like Néel's SD and MD theories, they do not allow an intuitive understanding of the underlying reasons for the remanence, as the results are obtained purely numerically; and (4) they require a level of detail of sample characterization to be run that is well beyond all but the most advanced paleomagnetic studies and hence are of limited use for most studies.…”
Section: Introductionmentioning
confidence: 99%